Association between maternal migraine and infantile colic: a narrative review - Farnoosh Emami; Kamyar Kamrani; Nahideh Khosroshahi (BMC Pediatrics)
Abstract Background Infantile colic (IC) is a common and distressing condition characterized by excessive crying and fussiness in otherwise healthy infants, typically resolving by three to four months of age. The etiology of IC remains poorly understood, but shared mechanisms with maternal migraine, such as genetic predisposition, sensory hypersensitivity, and gastrointestinal dysregulation, suggest a potential association. This narrative review aims to explore the relationship between maternal migraine and IC, summarizing current evidence and potential underlying mechanisms. Methods A comprehensive search was conducted in electronic databases, including PubMed, Scopus, Web of Science, and Google Scholar, from 2010 up to August 22, 2024. Studies were included if they investigated the association between maternal migraine and IC, included human participants, and were published in English. Case-control and cross-sectional studies providing original data were narratively analyzed. Data extraction focused on study characteristics, maternal migraine and IC definitions, and key findings. Results Out of 792 screened studies, 8 met the inclusion criteria, including 5 case-control and 3 cross-sectional studies. Most studies demonstrated a significant association between maternal migraine and IC, with maternal migraine increasing the likelihood of IC by 2.6 to 5 times. Proposed mechanisms include dysregulation of the trigeminovascular system, sensory hypersensitivity, disrupted sleep-wake cycles, and shared genetic predisposition. Evidence for paternal migraine’s role in IC was inconsistent, with most studies reporting no significant association. Conclusions The findings suggest a strong and consistent association between maternal migraine and IC, potentially driven by shared genetic, neurological, and environmental factors. IC may represent an early-life manifestation of migraine-related syndromes. However, variability in study designs and methodologies limits the generalizability of these findings. Future longitudinal and mechanistic studies are needed to clarify the pathways linking maternal migraine to IC and to explore potential interventions for at-risk infants.